The problem of hanging out with the crowd - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case centers on examples of crowd crush. It refers to accidents taking place during concerts, one in Ohio, USA, and another one in Denmark, with a particular focus on the crush at a Wal-Mart store during the Black Friday sales. How can businesses dealing with large crowds best protect their customers from these kinds of dangers?
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). The Problem of Hanging Out With the Crowd. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 287-290). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Crowd control -- Case studies; Consumer protection -- Case studies